Developmental environment shapes honeybee worker response to virus infection - Alexander Walton (Nature Portfolio, 2021)
Abstract The consequences of early-life experiences are far reaching. In particular, the social and nutritional environments that developing animals experience can shape their adult phenotypes. In honeybees, larval nutrition determines the eventual social roles of adults as reproductive queens or sterile workers. However, little is known about the effects of developmental nutrition on important adult worker phenotypes such as disease resilience. In this study, we manipulated worker developmental nutrition in two distinct ways under semi-natural field conditions. In the first experiment, we restricted access to nutrition via social isolation by temporarily preventing alloparental care. In the second experiment, we altered the diet quality experienced by the entire colony, leading to adult bees that had developed entirely in a nutritionally restricted environment. When bees from these two experiments reached the adult stage, we challenged them with a common bee virus, Israeli acute paralysis virus (IAPV) and compared mortality, body condition, and the expression of immune genes across diet and viral inoculation treatments. Our findings show that both forms of early life nutritional stress, whether induced by lack of alloparental care or diet quality restriction, significantly reduced bees’ resilience to virus infection and affected the expression of several key genes related to immune function. These results extend our understanding of how early life nutritional environment can affect phenotypes relevant to health and highlight the importance of considering how nutritional stress can be profound even when filtered through a social group. These results also provide important insights into how nutritional stress can affect honeybee health on a longer time scale and its potential to interact with other forms of stress (i.e. disease).